Bridging the Post-Excavation Gaps: Structured Guidance and Training for Post-Excavation in Archaeology - May Keith; Taylor James; Aitchison Kenneth (Open Archaeology)
This article explores the pressing need for consistent structured guidance and training in post-excavation (PX) skills within the field of archaeology. This need was identified through consultations with commercial practitioners facilitated by the Federation of Archaeological Managers and Employers as part of the Archaeologist’s Guide to Good Practice (AG2GP-Handbook) project. Through collaborative work with a range of archaeological practitioners across the UK, within the limits of a 1-year AHRC/UKRI budget, the project has successfully developed prototype online resources at https://archgoodpractice.com/ that embody and promote FAIR and sustainable best practices within the commercial archaeological sector for wider public benefit and use internationally. PX skills are critical for transforming and synthesising raw field data into meaningful insights about the past. The AG2GP-Handbook project focused on improving stratigraphic analysis, but this work highlighted that current educational and professional training across the UK, and beyond, often falls short of equipping archaeologists with these capabilities. The article examines related key challenges, such as gaps in university education and continuing professional development, that leave graduates and junior field practitioners ill-prepared for professional PX demands and with a very limited grasp of how their records in the field should be used afterwards.